Restructuring of industry space in selected cities of the Kujawsko-Pomorskie province during the period of political system transformation - Gierańczyk, Wiesława (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2006)
The period of system transformation in Polish economy had a great influence on the function of settlement systems. At the beginning of 1990s, the rules and mechanisms of cities development were changing, and their functional meaning in local and regional space was connected with introducing new market rules and changing the ownership system.Functional structure analysis in cities proves that industry is giving way. However, industry should not be treated as a decadent branch, and all legislative and investment actions ought to be concentrated on quality restructuring. Industry can compete on the local, national and European market only when it goes through structural transformation, from a simple industry based on raw materials to competitive industries of high technology. In the region, the openness to actions of innovation is manifested in the creation of the Bydgoszcz Industrial-Technical Park in Bydgoszcz and the Centre of Technology Transfer in Toruń.These units are to be the platform of cooperation between science and industry, to introduce the modern know-how to the region, to create new workplaces, and finally to upper the cities and region’s position on the industrial arena.